PENGARUH PENYULUHAN GIZI DENGAN MEDIA VIDEO TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG KONSUMSI SAYUR DAN BUAH DI SMAN 1 PALANGKA RAYA - Harlyanti Muthma'innah Mashar (Jurnal Gizi dan Pangan Soedirman, 2021)
The age of 10-18 years is the age range of adolescents who are included in the period of being vulnerable to nutrition. Habits at this age are often skipping breakfast, not moving, and snacking a lot. This causes low consumption of vegetables and fruits. This study aims to analyze the effect of providing nutrition counseling using video media on the knowledge and attitudes of adolescents about vegetable and fruit consumption at SMAN 1 Palangka Raya. The design of this study was a quasi-experiment with one group pretest and posttest design with 38 subjects. The results were then analyzed using the Wilcoxon test and McNemar test. The results showed that the characteristics of the subjects were in the age group of 15-17 years with the highest number aged 16 years (68.4%). Most of the subjects were female (55.3%). The results of the statistical test obtained p = 0.000 (p <0.05) stating that there was a significant difference between knowledge before and after counseling. The results of statistical tests using McNemar's test for attitudes obtained a p-value of 0.000 (p <0.05) which indicated that there was a significant difference between attitudes before and after counseling. Based on these results, counseling with video media influences the knowledge and attitudes of adolescents regarding the consumption of vegetables and fruits at SMAN 1 Palangka Raya.